Burden of proof in criminal proceedings in Malaysia : a review / Khairul Azman Kamaluddin - Kamaluddin, Khairul Azman (Faculty of Law, 1984)
The problems arising from the interpretation of the court in reference to the question of burden of proof in criminal proceeding has led many judges and writers to interprete the subject differently. Thus the aim of this project paper is to review the decisions of the various jurisdictions in England and Malaysia especially and to discuss the various judgements and commentaries that were put forward for the purpose of showing the problem. Although the topic directly concerns the burden of proof in criminal proceeding, the writer felt that it is important to review first the basic and broad principle regarding the burden of proof under the law of Evidence and only in the later chapters, the writer discusses the position in England and (in detail) in Malaysia. It is not the intention of the writer to limit the scope on the subject to Malaysian Jurisdiction only since the decision in other common law countries like Ceylon and India have in fact upon appeal to the Privy Council had its effect in the Malaysian cases. Thus the cases and material here does not only concern the Malaysian authority but also involve cases from England, India, Ceylon and Singapore. The preparation and the completion of this project paper is mainly done at the Perpustakaan Tun Abdul Razak, ITM, Shah Alam and writer is deeply in debt to Mr. Hardial Singh, the writers supevisor for all the assistant given. The writer also would like to thank Mr. Shad Salim Al Faruqi, the course tutor for being very cooperative and not to forget all the collegues who have given the encouragement to the writer to complete this project.